Considerations on the backscattered wireless communication links. Issue 3 (28th January 2013) - Duroc, Yvan; Vera, Gianfranco Andia
Abstract This article presents a study of the backscattered wireless communication links, in far‐field conditions, emphasizing new approaches.General expressions for forward and return link on the reradiating coexistence of antennas are presented. A formulation for the radar cross section parameter is proposed for taking into account the phase information in modeling. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:554–559, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27367